"TANGO" nocturia scanning tool: Turkish validity and reliability study. Issue 1 (5th August 2020) - Culha, Mehmet Gokhan; Culha, Yeliz; Buyukyilmaz, Funda; Turan, Nuray; Bower, Wendy
Abstract: Background: The aim of this study is to evaluate the validity and reliability of the Targeting the Individual's Aetiology of Nocturia to Guide Outcomes (TANGO) screening tool, which is used to determine nocturia etiology. Methods: Patients hospitalized in urology, orthopedics, and general surgery clinics between September 2019 and January 2020 were included in the study. Demographic characteristics of the participants such as age, gender, drug use, and nocturia severity were assessed by the researchers. The Turkish version of the TANGO questionnaire consisting of 22 questions was filled in by the patients. The patients were asked to repeat the same test 4 weeks later. Results: A total of 124 patients were included in the study. The mean age of the patients participating in the study was 51.20 ± 18.50 (38‐82). The result of the reliability assessment showed that the total score intraclass correlation coefficient was 0.715 (individual item score weighted kappa coefficients, 0.696‐0.731) and the Cronbach's alpha coefficient was 0.727. A total of 112 patients filled in the TANGO screening tool again after 4 weeks. The test‐retest reliability analysis kappa value was 0.75 (0.68‐0.83). In the validity analysis, a moderately positive correlation was observed between the TANGO‐Urinary Incontinence Score and the number of nocturia (r = 0.452, P = .003). Conclusion: According to the validation study, the TANGO screening tool is valid and reliable to determine the nocturia etiology for the Turkish population.